Illustrated key to the species in the genus Salapia Stål, 1865 (Heteroptera: Coreidae: Acanthocephalini), with descriptions of three new species - Brailovsky, Harry; Barrera, Ernesto (Zootaxa, 2023)
The genus Salapia Stål 1865 (Coreidae: Acanthocephalini) is redescribed and three new species are described: S. fundita from Ecuador, S. ignava from Peru, and S. nitella from Brazil. A revised key to all 21 species is included. Dorsal view photos of each known are provided.